ΔΙΑΚΡΙΤΙΚΗ AS A ΠΟΙΗΤΙΚΗ ΤΕΧΝΗ IN THE SOPHIST. (May 2020) - Zaks, Nicolas
Abstract : The διακριτικὴ τέχνη (the art of separating or discriminating), from which the sixth definition of the Sophist starts (226b1–231b9), is puzzling. Prima facie the art of separating does not fit the initial division of art between ποιητικὴ τέχνη (production) and κτητικὴ τέχνη (acquisition) at 219a8–c9. Therefore, scholars generally agree that, although mutually exclusive, ποιητική and κτητική are not exhaustive and leave room for a third species of art, διακριτικὴ τέχνη, on a par with ποιητική and κτητική. However, I argue that textual evidence suggests otherwise.